Muslims' Inheritance Law in Mindanao - Philippines: A Guide for Beginners - Pumbaya, Aliah Maruhom; , Prof. Dr. Suparman Syukur, M.A (2014)
This study was generally design to simplify one of the complex branches of Islamic Law (Shari'ah) - Inheritance. The main objective of this study is to discover and explore the Muslims' Inheritance law in Mindanao - Philippines as a guide for beginners. Although Philippines is Christian dominated country, the Code of Muslim Personal Laws of the Philippines also known as P.D. 1083 has been introduce in 1977. Before that, there was not even a single set of comprehensive codification of rules available on Islamic law specifically on Islamic law of Inheritance for the Muslims in Mindanao - Philippines in general. Due to lack of moral teachings and learnings, lack of awareness and lack of English textbooks and review materials on Islamic Inheritance in Mindanao - Philippines, the researcher chooses this topic rather than any other because it has been neglected and because it has been discussed but not properly or fully. This study seeks to answer the following questions, namely: 1) What are the Muslims' Inheritance laws in Mindanao - Philippines?; 2)What are the Islamic Rulings on Muslims' Inheritance laws in Mindanao - Philippines?; 3)What are the requisites of succession for Muslims' Inheritance laws in Mindanao - Philippines? and 4)What are the Procedures of Succession on Muslims' Inheritance law in Mindanao - Philippines? This study uses conceptual approach, statute approach and legislation approach to seek information in order to answer the research questions. To answer the problems mentioned above in this study scientifically, hence the researcher used the following data sources: first, the data sources which are adopted as a binding law such as P.D. 1083 otherwise known as the Code of Muslim Personal laws of the Philippines and from Holy Qur - an and Prophetic traditions (Hadith), Qiyas and Ijma on Islamic law of Inheritance; Second, the data sources which are adopted as a results of study through many books, literatures, magazines, journals, newspapers, and thesis. Third, the data sources which are explanations from primary and secondary materials such as encyclopedia and dictionary. The qualitative data taken from the data sources are analysed through logical analysis. The analytical tools used are as follows: first, legal interpretation; Second, theological interpretation; and finally, juridical analysis. The result shows that the Muslims' Inheritance law in Mindanao - Philippines was codified and became a binding law in 1977. The codification of Muslim Personal Laws is one of the greatest achievements of the Muslims in the Philippines. A total of 47 codified Islamic laws on Inheritance can be found in Book III of Presidential Decree 1083 otherwise known as The Code of Muslim Personal Laws of the Philippines. These are from article 89 to article 136. The Islamic Rulings on Muslims' Inheritance law in Mindanao - Philippines are commandments of Allah (S.W.T.). There are thirty-five verses of the Quran which refer to Mirath or its derivatives in one form or the other. There are 3 main verses in the Quran giving specific details of inheritance shares (4:11-12, 4:176). At least seven verses (2:180-182, 2:240, 4:33, 5:106-107) deals directly to testamentary disposition. Some of the Islamic rulings are taken from Prophetic Traditions, Qiyas, Ijma and Ijtihad like that of Special Cases. The Requisites of Succession for Muslims' Inheritance Law in Mindanao - Philippines is that the death of the decedent is ascertained; the successor is alive at the time of the death of the decedent; and the successor is not disqualified to inherit. The Procedures of Succession on Muslims' Inheritance Law in Mindanao - Philippines is that under the Code of Muslim Personal Laws of the Philippines, the order of preference of claims mentioned in Article 135 and Procedures for distribution of estate is as follows: "The estate of a decedent shall be applied to claims and charges in the following order: (a) Unpaid taxes; (b) Reasonable funeral expenses; (c) The expenses for probate, administration and other judicial expenses; (d) The debts of the decedent; (e) The legacies to the extent of the disposable one-third; (f) The distribution of shares among heirs; and (g) Unpaid dower." When distributing shares, we encounter four main situations, namely: Inheritance is distributed only amongst Dhul-Fard (Primary Heirs); Inheritance is distributed amongst Dhul-Fard and Al-Asabat Nasabiyyah; Inheritance is distributed only amongst Al-Asabat Nasabiyyah and Inheritance is distributed amongst Dhawul-Arham. Finally, if there are no distant kindred or still some residue left, then it goes to Bait-ul-Maal. Partition and Settlement of Special Cases on Muslims' Inheritance Law in Mindanao - Philippines varies depending upon on the case may be. It is important to note that if there are differences of opinions among the Orthodox School (madhahib) on Islamic Inheritance, the degree of authenticity of the Islamic evidence is given with much preference over the opinions of the madhahib. Therefore, although most of the Muslims in Mindanao - Philippines are following the Shafi'i Madhhab, the degree of authenticity of the Islamic evidence is given with much preference over the opinion of him.